One-punch man. 27, Tornado full blast - ONE, 1986- (Shonen Jump manga., 2024)
Psychos intends to fuse with Orochi, the Monster King, which would give them immense power against Tornado. Superalloy confronts Garo and experiences fear of his opponent's strength; meanwhile, Saitama gets caught up in a cave-in in the Monster Association's underground labyrinth.